2004
DOI: 10.1103/physrevlett.93.245901
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioCalculations to Model Anomalous Fluorine Behavior

Abstract: Implanted fluorine is observed to behave unusually in silicon, manifesting apparent uphill diffusion and reducing diffusion and enhancing activation of boron. In order to investigate fluorine behavior, we calculate the energy of fluorine defect structures in the framework of density functional theory. In addition to identifying the ground-state configuration and diffusion migration barrier of a single fluorine atom in silicon, a set of energetically favorable fluorine defect structures were found (F(n)V(m)). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Fluorine is a candidate codopant due to its very high electronegativity. Numerous previous studies [135][136][137][138][139][140][141][142][143] investigated the impact of F doping and codoping in Si with F providing evidence on the formation of F n V m clusters. Experimental work 136 on F-implanted preamorphized Si determined that the formation of F n V m clusters is detected.…”
Section: Codoping With Fluorinementioning
confidence: 99%
See 1 more Smart Citation
“…Fluorine is a candidate codopant due to its very high electronegativity. Numerous previous studies [135][136][137][138][139][140][141][142][143] investigated the impact of F doping and codoping in Si with F providing evidence on the formation of F n V m clusters. Experimental work 136 on F-implanted preamorphized Si determined that the formation of F n V m clusters is detected.…”
Section: Codoping With Fluorinementioning
confidence: 99%
“…112 This is consistent to Si, where again the bond-center configuration is prevalent. 139,140 The F 2 interstitial pair consists of a bond-center and a tetrahedral interstitial, which are oppositively charged and attract each other with a binding energy of À0.97 eV. 112 The positively charged bond-center F interstitials attract the doubly negatively charged V (dominant in Ge under intrinsic and n-type doping conditions, Fig.…”
Section: Codoping With Fluorinementioning
confidence: 99%
“…9 These evidences are supported by ab initio calculations, which have shown that in c-Si, F atoms preferentially form complexes with V ͑indicated as F n V m ͒, due to their great ability in saturating Si dangling bonds ͑dbs͒, rather than bind with Is or B or F. 10 Indeed, the somewhat high binding energy of these F n V m configurations, having all dbs decorated by F, makes them highly stable. 11 In literature, all experiments devoted to the understanding of the F behavior are done with F implanted in crystalline or preamorphized Si matrix. The only experiment realized in amorphous Si ͑a-Si͒ has been conducted by Nash et al, who studied the transport of F using secondary ion mass spectrometry ͑SIMS͒ and showed by TEM that F transport is influenced by F "inclusions."…”
Section: Formation and Evolution Of F Nanobubbles In Amorphous And Crmentioning
confidence: 99%
“…In the F0 center, a fluorine atom forms a Si-F bond inside a V 2 space. 6,13 Since this bond is nearly along the original Si-Si bond, the 19 F hyperfine splitting of F0 showed approximately a h111i axial symmetry. 13 Consequently, the hyperfine splitting was maximized in the [111] direction ($55 ) and was minimized in the normal direction to [111] (90 À 55 ¼ 35 ).…”
Section: Fig 2 (A)mentioning
confidence: 97%
“…4 Controlling of such damage caused by RIE is one of the major challenges for advanced scaled LSIs. Both carbon and fluorine atoms can create lattice defects 5,6 and may become the source of the leakage currents of p-n junctions. 2,7 However, microscopic entities of such defects are still unclear.…”
mentioning
confidence: 99%